Training on Improving Artificial Intelligence Literacy in Supporting 21st Century Learning for Students at SMAN 6 Central Bengkulu - Ahda, Netriani Veminsyah; Medriati, Rosane; Purwanto, Andik; Putri, Desy Hanisa; Siregar, Dennis Jovani Harryson; Pajri, Ahmad Khairul (CV Media Inti Teknologi, 2025)
Background of Study: The utilization of artificial intelligence (AI) in physics learning in Indonesia is still relatively new and requires further implementation regarding its effectiveness, so that it becomes a challenge in itself, especially in understanding abstract concepts and materials.Aims and scope of paper: The Chatbots and AI Visualizations training at SMAN 6 Central Bengkulu aims to improve students' skills and knowledge in utilizing modern technology to deepen their understanding of physics concepts.Methods: This study used a quantitative approach through pre-test and post-test of 41 students in grades X and XI, with instruments in the form of multiple-choice questions to measure basic understanding of AI, ability to write prompts, understanding and visualization skills on physics concepts, and understanding the ethics of using AI in learning activities.Results: The results showed high enthusiasm and interest in AI-based learning, with all respondents expressing interest in this technology. After the training, there were improvements in the understanding of physics concepts through AI, the ability to write prompts, understanding and visualization skills using AI, and ethical knowledge in the use of AI in learning.Conclusion: The findings indicate that the integration of AI in physics learning not only increases the effectiveness and interactivity of the learning process, but also equips students with relevant 21st century competencies in the digital era.